(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud Computing has become an important infrastructure in today’s computing. Globally, the computation is moving towards the Cloud Architecture. It is required that we utilize the methodology to get better results in computing environment and making it applicable in various branches. The main thing to take into account is the security where a few security issues related to cloud computing are derived from the ways used to create such actions; it includes how the methods are scheduled and what type of data can be adopted in cloud. If security is not durable and uniform, the flexibility and merits that cloud infrastructure has to give will have small dependability. In this paper we try to direct and establish the important security matters and provide some kind of solutions in this computing methodology and give a view on the ongoing trends for security in this technological outbreak